2014
DOI: 10.1016/j.forsciint.2013.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Search protocols for hidden forensic objects beneath floors and within walls

Abstract: The burial of objects (human remains, explosives, weapons) below or behind concrete, brick, plaster or tiling may be associated with serious crime and are difficult locations to search. These are quite common forensic search scenarios but little has been published on them to-date. Most documented discoveries are accidental or from suspect/witness testimony. The problem in locating such hidden objects means a random, or chance-based approach is not advisable. A preliminary strategy is presented here, based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 22 publications
1
20
0
3
Order By: Relevance
“…Recent geophysical research using simulated clandestine graves have found optimal detection methods and configurations are highly variable, depending upon a host of factors, the most important deemed to be time since burial, burial style, local soil type, vegetation and climate [35,[43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Recent geophysical research using simulated clandestine graves have found optimal detection methods and configurations are highly variable, depending upon a host of factors, the most important deemed to be time since burial, burial style, local soil type, vegetation and climate [35,[43][44][45][46][47][48][49][50][51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…Near-surface geophysical methods rely on there being a detectable physical contrast between the target and the background (or host) materials (see [37]). Near-surface geophysical surveys have been used to try and locate clandestine graves in a number of reported criminal search investigations (17)(18)(19)(20)(21)(22)(23)25,26,(38)(39)(40)(41)(42). Geophysical surveys collected over simulated burials have also been undertaken to collect control data (e.g., [15,[43][44][45][46]).…”
mentioning
confidence: 99%
“…Actualmente, se ha sumado el desarrollo de estudios geofísicos en fosas clandestinas de prueba para elaborar metodologías más precisas de ubicación de estos sitios y que aumenten la posibilidad de hallazgo considerando varios factores como antrópicos, de enterramiento y climáticos, entre otros (Davenport et al, 1992;Murray y Tedrow, 1992;Strongman, 1992;Pye y Croft, 2004;Ruffell y McKinley, 2008;Schultz, 2008;Schultz y Martin, 2011, 2012Pringle et al, 2012Pringle et al, , 2015Ruffell et al, 2014;Hansen et al, 2014). En Colombia los primeros ensayos empíricos para la ubicación de enterramientos clandestinos, fueron realizados aplicando métodos geofísicos en fosas simuladas, entre éstos: magnético, electromagnético, resistividad eléctrica y georradar (Molina et al, 2012(Molina et al, , 2015Molina, 2016).…”
Section: Antecedentesunclassified